«Помилка» Лесі Українки: до проблеми жанрової особливості - Шахова, Катерина; Shakhova, Kateryna (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглянуто жанрову своєрідність твору Лесі Українки «Помилка (Думки арештованого)». Встановлено ознаки жанру записок, проаналізовано архітектоніку твору й специфіку оповіді, визначено роль психологізму в моде- люванні я-концепції наратора, розкрито функцію й семантику назви. The article deals with the genre originality of Lesіa Ukrainka’s “Mistake (Prisoner thoughts)”. It defines the notes genre features: self- concept as the organizing factor of narrative; the first person narration determines privacy and confession; reflexivity, self-characteristic; the image of narrator (the author of notes) is self-awareness; recording act is inseparable from the text. It analyzes the architecture of composition, which consist of two parts. The first part depicts the narrator’s thoughts and feelings during writing notes. Second part (memory) involves recipient to hero’s retrospective introspection. Writing of notes for him is a kind of attempt to understand himself and his causes of a fatal mistake. The narrator’s self-concept forms through contrasting image of revolutionary woman he loved. Lesіa Ukrainka reveals the dramatic moments of crisis of creative personality, she invests in protagonist’s notes a lot of her thoughts about the specifics of artist psychology, including a conflict of personal and public interests.
“Mistake (Prisoner’s Thoughts)” by Lesіa Ukrainka: the Problem of Genre Feature
Keywords: жанр; записки; наратор; я - концепція; психологізм; genre; notes; narrator; self-concept; psychology